Effect of Magnesium Oxide-Carbonized Hibiscus Sabdariffa (Zobo) Waste and Magnesium–Zinc Binary Oxide Nanocomposites in Mitigating Cadmium and Bacteria in Contaminated Water. (Lafia Journal of Scientific and Industrial Research, 2025)
The need for active and inexpensive materials in combating menace of bacterial as well as heavy metals is very essential to the longevity of man and protection of his environment against deleterious substances such as bacterial and heavy metals. This research was designed to study the mitigative effect of MgO-carbonized zobo waste nanocomposite (MOCZWNC) and Mg-Zn binary oxide nanocomposite (MgZBONC)  on Salmonella typhi – gram negative organism and Staphylococcus aureus – gram positive organism as well as eradication of cadmium ions in contaminated water. MgZBONC and MgOCZWNC was prepared, characterized and their adsorption ability was studied using adsorption isotherm evaluation. The mitigative effect of MgOCZWNC and MgZBONC on bacteria was evaluated using turbidimetric method. The maximum sorption capacity of MgOCZWNC and Mg-ZBONC for cadmium was 188.68mg/g and 192.31mg/g respectively. The average crystallite size of MgOCZWNC and MgZBONC was 28.61nm and 59.42nm respectively. The treated samples brought about a steady decrease in the population of Staphylococcus and Salmonella within 2hrs, after about 2hrs, the samples of staphylococcus and salmonella treated with MgOCZWNC continued to show continuity in its mitigative effect at decreasing the population of the bacteria with time while the staphylococcus and salmonella sample treated with MgZBONC experienced a slightly steady drop in their effectiveness after same Nanocomposite period. The MgZBONC adsorbed cadmium ions more effectively and the MgOCZWNC was more efficient in severely reducing the population of staphylococcus and salmonella in contaminated water.